'Footnotes to Miller and Moore': Monomyth and Transnationality in the 1986 Superhero Comics. (1st October 2016) - Francis, Fred
Abstract: New developments in comics studies have begun to consider the superhero comic as a transnational, rather than American, phenomenon. This approach offers a new way of thinking about the typical story that Frank Miller's The Dark Knight Returns and Alan Moore's Watchmen jointly upended the comics world in 1986. While there is robust criticism to challenge the idea that 1986 was a miraculous year for comics, the continuing attention drawn by the two works requires us to think further about their apparent similarity. This article proposes the importance of a narrative of American exceptionalism within comics culture as a defining feature of the contemporary context for the production of the works. It then examines their responses to this context, arguing that they undermine the American monomyth of the superhero in different ways that originate in the different national positions of the two writers.